High performance coach cognition in the wild: using applied cognitive task analysis for practical insights–cognitive challenges and curriculum knowledge - Taylor, Jamie; Ashford, Michael; Jefferson, Matt (Frontiers in Psychology, 2023)
Despite significant empirical work in the sport coaching domain, there remains a paucity of evidence to inform practice in high-performance sport coaching. As a result, there are gaps in our understanding regarding coaching expertise at different levels of athlete performance. A significantly underutilised tool in coaching research are Cognitive Task Analysis knowledge elicitation tools. Addressing these concerns, here we utilise Applied Cognitive Task Analysis and a semi-structured interview protocol to elicit the cognitive challenges and use of knowledge by a group of N=7 high-performance endurance sport coaches from a single national governing body. Analysis suggested prominent and ongoing challenges in day-to-day practice which, in turn require significant adaptive skill. In addition, results show how coaches used knowledge flexibly and conditionally to meet the demands of their role. A novel finding being the identification of the use of curriculum knowledge to mentally project the needs of athletes. The findings suggest opportunities for the use of Cognitive Task Analysis in sport coaching and further exploration of the cognitive challenges of coaching to influence the progress of coach development practice.